THE ANALYSIS OF SOCIAL CONFLICT PORTRAYED IN ROBERT FROSTâS SELECTED POEM - Dewi, Citra; Kaskumita, Rina (LITERARY CRITICISM, 2015)
Social conflict is an event that we often overcome in our daily life. People usually face the social conflict by many attitudes. There are three kinds of social conflict, they are conflict between individual, inter-group conflict, and conflict between organizations. There are many ways of someone to express their thought about social conflict, One of them is by using beautiful combination of words that contains implicit meaning that makes that combination of words is hard to be understood. One of the famous poets is Robert Frost. Robert frost beautifully uses combination of words and metaphor to express his thinking of social conflict. By using descriptive qualitative method, the researcher is helped to pill off the meaning of the poem that closely related to social conflict in the selected poem of Robert Frost. After having analysis over the entire related source in this case in this case is poem, the researcher found that there is a tendency of the author of the poem, Robert Frost, in using the social conflict sense in presenting the poem. The implicit point of social conflict in the poem, most of them is included to conflict between individual, then the rest is included to inter-group conflict. As said by That condition is analogously with the theory of social conflict that is conflict between individual that stated Conflict between individual is conflict that occurs between one individual, to another individual or more. This conflict is usually caused by confusing condition of someone (Rummel : 1991).Â Keywords : Social Conflict, Robert Frostâs Poem, Conflict between Individual